2011
DOI: 10.1093/carcin/bgr135
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of DNA methyltransferase and histone deacetylase restores caspase-8 expression and sensitizes SCLC cells to TRAIL

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising drug for the treatment of tumors; however, a number of cancer cells are resistant to this cytokine. Among the mechanisms of resistance of small cell lung carcinomas (SCLCs) to TRAIL is the lack of caspase-8 expression. Although methylation of the caspase-8 promoter has been suggested as the main mechanism of caspase-8 silencing, we showed that reduction of the enzymes involved in DNA methylation, DNA methyltransferases (DNMT) 1, 3a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 36 publications
4
48
0
1
Order By: Relevance
“…To further investigate whether aberrant methylation of HOXA1 is necessary in multidrug resistance, we knocked down HOXA1 in the context of 5-aza-CdR treatment, and the results showed that there is no significant difference between control groups and siHOXA1-5-Aza-CdR groups in H446AR cells upon CDDP and ADM treatment. In addition to caspase-8 reported by Kaminskyy et al, 23 our results suggested DNA methylation of HOXA1 was closely associated with chemoresistance of SCLC.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To further investigate whether aberrant methylation of HOXA1 is necessary in multidrug resistance, we knocked down HOXA1 in the context of 5-aza-CdR treatment, and the results showed that there is no significant difference between control groups and siHOXA1-5-Aza-CdR groups in H446AR cells upon CDDP and ADM treatment. In addition to caspase-8 reported by Kaminskyy et al, 23 our results suggested DNA methylation of HOXA1 was closely associated with chemoresistance of SCLC.…”
Section: Discussionsupporting
confidence: 76%
“…For example, DNA methylation of caspase-8 in SCLC cells resulted in resistance to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). 23 We found that downregulation of HOXA1 gene affects SCLC cell survival and chemoresistance before. 16 In our study, BSP method showed hypermethylation status of HOXA1 CpG islands in the resistant cells as compared with the parental cells.…”
Section: Discussionmentioning
confidence: 77%
“…5′aza is often used in combination with HDAC inhibitors such as Trichostatin A (TSA), to induce the re-expression of epigenetically silenced genes. 7 MicroRNAs (miRs) are small noncoding RNAs that inhibit protein expression by posttranscriptional inhibition. They are fundamental regulators of diverse cellular processes, whose deregulation contributes to many human diseases including cancer.…”
mentioning
confidence: 99%
“…Moreover, the combination of these two epigenetic drugs sensitized SCLC cells to TRAIL. 38 The most efficient combinatorial treatments are summarized in Table 3.…”
Section: The Oncodeath Projectmentioning
confidence: 99%